1997
DOI: 10.1002/(sici)1098-108x(199703)21:2<103::aid-eat1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The superior mesenteric artery syndrome and acute gastric dilatation in eating disorders: A report of two cases and a review of the literature

Abstract: Objective The pathophysiology and symptomatology of the superior mesenteric artery syndrome (SMA syndrome) is discussed. A review of much of the available literature concerning the SMA syndrome and the associated condition acute gastric dilatation is offered. Results: Two new cases of acute gastric dilatation in patients with eating disorders, one of whom was diagnosed with SMA syndrome, are presented, along with a discussion of these conditions in reference to the eating disorders. Conclusion: The SMA syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
77
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 24 publications
1
77
0
2
Order By: Relevance
“…4,5 Some previous studies demonstrated that SMA (superior mesenteric artery) syndrome was associated with emaciation and was an underlying cause of increased intragastric pressure, which is a contributing factor of acute gastric dilatation. 11,12 Although other factors may be involved, the combination of all of the above factors was likely to be important in this case.…”
Section: Discussionmentioning
confidence: 89%
“…4,5 Some previous studies demonstrated that SMA (superior mesenteric artery) syndrome was associated with emaciation and was an underlying cause of increased intragastric pressure, which is a contributing factor of acute gastric dilatation. 11,12 Although other factors may be involved, the combination of all of the above factors was likely to be important in this case.…”
Section: Discussionmentioning
confidence: 89%
“…6 The second includes wasting conditions such as AIDS, 6 malabsorption, cancer, 7 cerebral palsy, and other conditions associated with cachexia; catabolic conditions such burns; 8 and with eating disorders such as anorexia nervosa and drug abuse. 9,10 Similarly, it has been described following surgery-associated rapid weight loss such as bariatric surgery, esophagectomy, and abdominal trauma. 11,12 Regardless of the etiology, once the condition has become established, it becomes selfperpetuating with a cycle of vomiting leading to further weight loss and thus further vomiting.…”
Section: Discussionmentioning
confidence: 98%
“…Food intolerance promotes ongoing weight loss, which may further reduce intraabdominal adipose tissue and exacerbate the problem, resulting in a vicious cycle and deterioration in clinical condition. 5,9,13,14 Diagnosis is frequently delayed, relies on a high index of suspicion, and is often made by a process of exclusion. The differential diagnosis includes megaduodenum 15 and other more common conditions including chronic pancreatitis and peptic ulcer disease.…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal X-ray may reveal a large air-fluid level that belongs to the fundus of the stomach, and subdiaphragmatic free air in cases with perforation. The most useful imaging modality is abdominal computed tomography, which is not only useful in diagnosis but also in revealing the etiology (6). Endoscopy is important for visualization of the gastric mucosa (7).…”
Section: Discussionmentioning
confidence: 99%